Biomass Energy Dependence in South Africa: Are the Western Cape Province households descending the energy ladder after improvement in electricity access?. (December 2020) - Muazu, N.B.; Ogujiuba, K.; Tukur, H.R.
Abstract: South Africa was considered to have attained universal access to modern energy from 1994 to 2012. This meant that the number of households that moved away from the use of dirty energy to clean energy for domestic activities has drastically increased "ascending the energy ladder". However, recent trends in household energy consumption in many developing countries are showing many households have either retained or are reversing to fuelwood use despite the modern energy access "descending the energy ladder". Against this backdrop, the present study evaluates whether or not South African households are still using fuelwood for domestic activities" descending the energy ladder" even after the rapid improvement in electricity access. Both theoretical and empirical literature suggests that households in developing countries often choose their energy type based on certain factors. We take this assumption to test in the Western Cape Province by employing a quantitative cross-sectional survey design involving a structured questionnaire from 1199 fuel-wood household consumers. The findings revealed that electricity access has made households to "move up the energy ladder" instead of "descending the energy ladder" for the reasons of household marital status, size of the household, household income, and employment status of the household. The study recommends more investment in human capital to enable households to have easy access to modern clean energy.